2007
DOI: 10.1590/s1415-47572007000600022
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Eupemphix nattereri (Amphibia, Anura, Leiuperidae) from Central Brazil

Abstract: This study reports on 156 specimens of the amphibian Eupemphix nattereri, a widely distributed leiuperid, obtained from 11 municipalities of central Brazil. The extent of genetic variation was quantified by determining the mean number of alleles per locus and the proportion of polymorphic loci. An analysis of molecular variance (AMOVA) was performed on the random amplified polymorphic DNA (RAPD) haplotypes. The genetic distances obtained by calculating pairwise Φst among local samples were used to determine po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…The genetic distance of Ae. aegypti in four cities in West Sumatra was high, similar to the previous study [52]. Genetic distance was high if the score was > 0.5.…”
Section: Correlation Of Geographical Distance With the Genetic Distancesupporting
confidence: 88%
“…The genetic distance of Ae. aegypti in four cities in West Sumatra was high, similar to the previous study [52]. Genetic distance was high if the score was > 0.5.…”
Section: Correlation Of Geographical Distance With the Genetic Distancesupporting
confidence: 88%
“…Short distance (less than 5 km) enabled the migration of individuals among populations and lead high gene flow to occur among populations. Previous studies had shown that geographical distance was significantly correlated with population structure (Silva et al, 2007;Telles et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…Some authors (Rowe et al 2000;Silva et al 2007) reported limited vagility to amphibians and many species maintain high fidelity to the local breeding, thus contributing to lowering gene flow among their populations. Hence, the low gene flow due to habitat fragmentation coupled with low vagility and decline of anuran species affects genetic diversity of these populations (Arens et al 2006;Silva et al 2007).…”
Section: Referências Bibliográficasmentioning
confidence: 99%